Mitys’ story - La Conte, Maria Giovanna (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
The Mitys’ story (Arist., Poet. 9, 1452a, 7-9), which exemplifies the dramatic θαυμαστόν, is likely to be the plot of a play that was really performed. This play antedates a feature of Hellenistic dramaturgy, viz. the choice of historical or contemporary events.